(untitled) (Journal of the College of Education for Women, 2019)
The city of Baghdad have several large Meanders river the most important and distinctive meander is Jadiriyah meander. the nature and direction of creep river Tigris River in Baghdad Was to determine over the last century by matching maps of ancient and modern, note the increased inflections intensity and slowly in the first half of the last century because of the impact of repeated high discharge and get the process of erosion in the concave side and the process of sedimentation in the convex side . After the middle of the last century high discharges decrease due to the construction of dams and reservoirs and hence the lower activity of the river and stopped the river and meandering process confined within the borders of the river course. The study of the evolution of the river through the history by linking the course with some of the known archaeological sites. Where he found four stages in the Jadiriyah meander the Babylonian and Abbasid, Ottoman, and modern, in a Kadhimiya meander found Abbasi meander, depending on the shrine of those who control Al kadimin mosque (the tomb of Quraish previously), while the rest of the meanders can be found through the use of the creep rate of its annual calculated in Kadhimiya meander and the value of creep of one meter per year. The course of the Tigris River between the areas of the Bab almoathem and the Karrada keep almost straight for the duration of the study and the lack of meandering it, is inferred from the presence of raised constructors irrigation Babylonian (dams) in the Bab almoathem and Abasiya Archaeological on extending the most important school Mustansiriya Abbasid Palace. Is characterized by Jadiriyah meander seating capacity and that no event has cut the neck to the entrance to the fact that deposits of mud torsion resistance to erosion of river, and thus Jadiriyah meander Older age of the rest of the meanders of Baghdad. It age estimated with an more than 2700 years old.